PENYULUHAN HUKUM TENTANG PERLINDUNGAN HAK-HAK ANAK MELALUI PENCEGAHAN PERKAWINAN USIA DINI PADA KALANGAN PELAJAR DI KOTA TIDORE KEPULAUAN - Salha Marasaoly; Faissal Malik; Sophian Y Selajar (Bajang Institute, 2022)
To transform knowledge to students about the protection of children's rights through the prevention of early marriage and to foster legal awareness of students / students so as to avoid behaviors that can have an impact on early marriage. This devotional activity is carried out by socializing methods directly to high school students in the city of Tidore Islands. Results of Devotion; There is still vulnerable and minimal information related to early marriage with various impacts on the physical, mental, and psychological development of children. The city of Tidore Islands is one of the small towns that also has a number of dispensation applications that although small compared to other cities but to anticipate a surge in applications, serious attention is needed by the local government.